2022
DOI: 10.1002/aps3.11467
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic confirmation of a biased phenotypic sex ratio in a dryland moss using restriction fragment length polymorphisms

Abstract: Premise In dioicous mosses, sex is determined by a single U (female, ♀) or V (male, ♂) chromosome. Although a 1 : 1 sex ratio is expected following meiosis, phenotypic sex ratios based on the production of gametangia are often female‐biased. The dryland moss Syntrichia caninervis (Pottiaceae) is notable for its low frequency of sex expression and strong phenotypic female bias. Here we present a technique to determine genotypic sex in a single shoot of S. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Recently, sex ratios in adult non-reproductive populations were reported for a few species, commonly exhibiting a female bias. Some studies indicated overall sex-independent expression rates ( Hedenäs et al , 2010 ; Bisang and Hedenäs, 2013 ; Bisang et al , 2015 , 2020 ), but in others, expression levels varied between sexes and regions (present study; Baughman et al , 2017 ; Ekwealor et al , 2022 ).…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Recently, sex ratios in adult non-reproductive populations were reported for a few species, commonly exhibiting a female bias. Some studies indicated overall sex-independent expression rates ( Hedenäs et al , 2010 ; Bisang and Hedenäs, 2013 ; Bisang et al , 2015 , 2020 ), but in others, expression levels varied between sexes and regions (present study; Baughman et al , 2017 ; Ekwealor et al , 2022 ).…”
Section: Discussioncontrasting
confidence: 42%
“…He hypothesized that males should have a higher mortality in severe conditions because they allocate more resources prezygotically in sexual reproduction than females, which could result in genetic deprivation. However, newer evidence showed that non-reproductive males occurred in similar frequencies to females in exposed microsites ( Ekwealor et al , 2022 ), and male rarity was probably attributable to lower male sex expression. Finally, restricted sexual recruitment in unfavourable environmental conditions might facilitate the evolution of ‘genetic sterility’ through selection against traits involved in sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the species Syntrichia caninervis Mitt. as a study system, Ekwealor et al ( 2022 ) provide a method for the sex classification of sterile shoots. Using a restriction fragment length polymorphism (RFLP) approach, the authors identified a locus on the sex chromosomes which they then used to develop targeted PCR primers to screen non‐expressing shoots.…”
mentioning
confidence: 99%